The Long Non-coding RNA Cytoskeleton Regulator (CYTOR) Sponges microRNA- 206 (miR-206) to Promote Proliferation and Invasion of HP75 Cells - Keqi, Hu; Handong, Liu (Current Cancer Drug Targets, 2021)
Background: The role and mechanism of long non-coding RNA cytoskeleton regulator (CYTOR) in Invasive Pituitary Adenomas (IPA) have not been elucidated previously. Objective: This study aimed to investigate the interaction between CYTOR and miR-206 and their roles in IPA using HP75 cells as the model. Methods: The expression levels of CYTOR and miR-206 were detected by quantitative real-time polymerase chain reaction (qRT-PCR) in IPA tissues and cell lines. The Chi-square test was used to analyze the correlation between CYTOR expression and clinical-pathological parameters. HP75 cell proliferation was detected by Cell Counting Kit-8 assay and colony formation assay. Scratch healing experiments and Transwell assay were used to detect migration and invasion of HP75 cells. The relationship between CYTOR and miR-206 was predicted by bioinformatics and verified by qRT-PCR and the dual-luciferase reporter gene method. Results: CYTOR is up-regulated in IPA tissues and cell lines. The high expression of CYTOR is associated with adenoma invasiveness and adenoma size of the patients. Down-regulation of CYTOR decreases the proliferation, migration and invasion of HP75 cells, while up-regulation of miR-206 can inhibit proliferation, migration and invasion of HP75 cells. MiR-206 is identified as a target of CYTOR and could be negatively regulated by it in IPA. Discussion: CYTOR, as a tumor-promoting factor, facilitates the proliferation, migration and invasion of HP75 cells through sponging miR-206. Conclusion: The CYTOR-miR-206 axis provides new insights into the diagnosis and treatment of IPA.
Keywords: invasion